Pengembangan Agrowisata Kampung Tapi Menuju Ekonomi Keberlanjutan Di Nagari Kamang Tangah Anam Suku, Agam - Bahari, Asniati; Gusmini; Luthan, Elvira; Novfirman; Ona Guserike Afner, Synthia; Esti Rahmaningsih, Dwi (PELITA NUSA TENGGARA, 2025)
This service program aims to develop Kampung Tapi as an agro-tourism village based on sustainable integrated farming. Kampung Tapi has great potential with fertile agricultural land, biodiversity, and rich local culture. However, the local community faces various challenges, such as unproductive yard land, limited skills in marketing products, and high dependence on the traditional agricultural sector. To address these issues, this program uses a participatory approach method through site surveys, socialization, training, mentoring, and periodic evaluation. The training provided includes integrated agricultural management techniques based on zero waste, making organic fertilizer from agricultural waste, and digital marketing through packaging and social media. This activity actively involves the Dasawisma group to ensure that the training material is not only understood, but can also be applied in daily life. It is hoped that through this service program, a significant increase in the technical, managerial, and marketing skills of the Dasawisma group and also the community of Kampung Tapi will be achieved. In addition, the active participation of the community in the management of local products becomes the main attraction of Kampung Tapi agrotourism, expanding the marketing network, and increasing income. This program not only provides economic benefits to the community, but also contributes to environmental sustainability and the development of Kampung Tapi as a leading agro-tourism destination. With the synergy between the agriculture and tourism sectors, Kampung Tapi is expected to become a model of a sustainable and inspiring agritourism village